2017
DOI: 10.1063/1.4979699
|View full text |Cite
|
Sign up to set email alerts
|

Dual traveling wave rotary ultrasonic motor with single active vibrator

Abstract: Traveling wave rotary ultrasonic motor with double vibrators can improve the output performance effectively. However, the rotor has to be energized through a slip ring, which increases the complexity and reduces the reliability. Inheriting the concept of two traveling waves propagating in the stator and rotor, a dual traveling wave rotary ultrasonic motor energized only in the stator is proposed. By analyzing the oscillatory differential equation and the contact particles motion, a traveling wave is found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The viscosity of the experimental water is inevitable, which also causes fluid flowing hysteresis. According to the literature [45,46] and the characteristics of the piezoelectric vibrator, another resonance may exist in the high-frequency region (around 1.8 kHz-2.1 kHz). By studying the amplitude of the piezoelectric vibrator, it was found that the amplitude decreases with the frequency increase, as shown in Figure 11, and the amplitude transformation period also decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity of the experimental water is inevitable, which also causes fluid flowing hysteresis. According to the literature [45,46] and the characteristics of the piezoelectric vibrator, another resonance may exist in the high-frequency region (around 1.8 kHz-2.1 kHz). By studying the amplitude of the piezoelectric vibrator, it was found that the amplitude decreases with the frequency increase, as shown in Figure 11, and the amplitude transformation period also decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum torque and speed under Modes C and D are both much smaller than that under Modes A and B. Compared with prior piezoelectric motors [15][16][17][18][19][20][21], this motor can be flaky shape, and driven by a miniaturized circuit. The most significant difference between this design and the former ones is that the motor possesses different performances under variable excitation ways and vibration modes, and then has wider applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these piezoelectric motors are driven by out-of-plane bending modes [12][13][14][15]. The stator is developed with a slim and long configuration, which probably restricts its application in in-vivo [15][16][17]. To limit the height of piezoelectric motors, a compact motor operating in the d15 shear-mode was designed [15].…”
Section: Introductionmentioning
confidence: 99%
“…High-power piezoelectric systems (HPPSs) are used in a large range of applications, such as ultrasonic welding, cutting and actuators [1][2][3][4]. In high-power situations, it is crucial to effectively convert the electrical energy into the mechanical vibration in the piezoelectric transducers (PTs) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%